Assessment of CMIP5 Models Based on the Interdecadal Relationship between the PDO and Winter Temperature in China - Yifei Xu; Te Li; Shuanghe Shen; Zhenghua Hu (Atmosphere, 2019)
In this study, the impact of the Pacific Decadal Oscillation (PDO) on the China winter temperature (CWT) was assessed on an interdecadal timescale, and the capacities of the 35 models of the fifth Coupled Model Intercomparison Project (CMIP5) were assessed by simulating the PDO-CWT teleconnection. The Met Office Hadley Centre’s sea ice and sea surface temperature (HadISST) were used as the observational data, and Climatic Research Unit (CRU) datasets provided long-term temperature data for the 1901–2005 period. By calculating the spatial correlation coefficient between the PDO index and winter temperature in China, thirteen CMIP5 models close to the HadISST datasets were selected for this study. These models were averaged as the good multi-model ensemble (GOODMME), and the PDO-CWT spatial correlation between the GOODMME and the observations was 0.80. Overall, the correlation coefficient between the PDO index and atmospheric circulation suggests that the GOODMME produces the same excellent results as do the observations. The results also verify the GOODMME’s superiority in simulating the impact of the PDO on winter temperatures in China. The possible mechanisms underlying the impact of the different phases of the PDO on the CWT are also described.